Women’s Empowerment and its Relationship to Intimate Partner Violence in Palpa District, Lumbini, Nepal - Gaha, Rekha; Das, Dorwin (Journal of Advanced Academic Research, 2024)
Background: Intimate partner violence (IPV) violates women's human rights and is a major public health concern. Intimate relationship violence or non-partner sexual assault affects about one in three (30%) women worldwide at some point in their lives. These types of violence harm women's sexual, emotional, physical, and reproductive health. This kind of abuse against women is preventable. Women's empowerment encompasses six common qualities: psychological, political, legal, economic, physical, and social empowerment, encompassing various aspects of life. Objectives: To assess the relationship between women’s empowerment and intimate partner violence. To identify the prevalence and contributing factors of intimate partner violence among married women. Materials and method: A descriptive cross-sectional study design was adopted for the study. The sample size was 352 and a purposive sampling technique was used to select the sample. Data was collected by face-to-face interviews using per-tested questionnaire during April, May, June, and July 2023. Questionnaire related to Socio-demographic information, Standard valid tool Conflict Tactics Scale tools (CTS) were used as instruments. Data were analyzed using descriptive and inferential statistics with SPSS version 22. Results: Out of 352 respondents, nearly half (43.2%) were between the ages of 30 and 39. Half of the respondents (50.3%) had low decision-making levels. Likewise, the lowest proportion of the respondents (16.2%) had a moderate level. More than half of the respondents (58.5%) had a low level of empowerment, whereas only 3.4% of the respondents had a high level of empowerment. Regarding violence, physical was 20.2%, sexual was 24.1%, emotional was 33.2%, controlling behavior was 53.7%, and overall intimate partner violence was 68.5%. There is a statistically significant relationship between intimate partner violence and women’s age (p =<0.010*), duration of marriage (p=<0.009*), socioeconomic class (p = <0.01*), member of the organization (p = 0.005*), bank account (p=0.006*), empowerment (p = 0.020*), husband's alcohol habit (p = <0.01*), and husband's smoking habit (p = <0.01*). Conclusion: Based on the findings of this study, it was concluded that more empowered women had less experience with intimate partner violence, whereas less empowered women had more experience with emotional, sexual, and physical abuse, as well as dominating actions from their close relationships. Having children, household decision-making, and property ownership had no noticeable effect on the prevalence of intimate relationship violence. The likelihood of intimate relationship violence was not significantly impacted by having children, making decisions, or possessing property.